Gamification and strengthening oral skills in English for childhood - Vergara-Pareja , Claudia Marcela; Nielsen-Niño, Jaddy Brigitte; Niño-Vega, Jorge Armando (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The research was aimed to identify the impact of implementing a gamified educational material to strengthen oral ability in English in childhood students. The study had a descriptive quantitative approach, with an initial and final test, which made it possible to determine the learning gain in 50 students between 4 and 6 years old, belonging to Colombian educational institution. The results showed a high range of learning, with a Hake factor of 0,736. Students improved their academic performance in terms of oral expression in English, referring to the criteria of: grammar, pronunciation, fluency and vocabulary. The above indicates that through gamified educational material, oral ability in English can be strengthened in childhood students. In other words, students, through play and interaction with content, acquire knowledge, abilities and skills that allow them to strengthen their cognitive development.